Analysis of anti‐tumour necrosis factor‐induced skin lesions reveals strong T helper 1 activation with some distinct immunological characteristics. (16th May 2018) - Stoffel, E.; Maier, H.; Riedl, E.; Brüggen, M.‐C.; Reininger, B.; Schaschinger, M.; Bangert, C.; Guenova, E.; Stingl, G.; Brunner, P.M.
Summary: TNF‐blockers have become a powerful and widely used treatment for many inflammatory diseases, including inflammatory bowel diseases and rheumatoid arthritis. While generally safe, one possible side effect consists of red, scaly patchy skin lesions that often look like psoriasis or eczema. These lesions can appear in up to one third of patients treated with TNF‐blockers over a time period of 10 years. The reasons why these skin lesions develop are still not completely understood. Researchers in Vienna and Zurich aimed to better characterize these lesions on several levels, including microscopic, cellular and molecular investigations. The researchers found that while most lesions indeed looked like eczema and psoriasis under the microscope, at a molecular level there were some characteristic differences from conventional psoriasis and eczema. In all of the lesions caused by TNF‐blockers, interferon gamma was present at high levels, a molecule that is a powerful inflammatory mediator produced by a specific set of immune cells. Results from this study might help to better guide future treatment approaches that can avoid such side effects. Abstract : Linked Article:  Stoffel et al. Br J Dermatol 2018;178 :1151–1162